2018
DOI: 10.15171/jrip.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Crimean Congo hemorrhagic fever: a brief report regarding kidney involvement

Abstract: In patients with CCHF, especially children, hematuria, proteinuria, oliguria and azotemia could have been found by urinalysis. Moreover, because of the fact that proteinuria and urine neutrophil gelatinase-associated lipocalin (uNGAL) levels could increase in children with CCHF; thus, monitoring of renal involvement related to CCHF by measurement of urine total protein and uNGAL is recommended. Please cite this paper as:Khazaei Z, Darvishi I, Amiri M, Sohrabivafa M, Kamran S. Crimean Congo hemorrhagic fever: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…CCHFV causes a fatal human infection with high mortality rate. Onset of disease coincides with sudden fever, myalgia, dizziness and bodyache leading to nausea, vomiting, diarrhoea, neural impairments, kidney and liver failure after 5th day of illness that is associated with higher mortality 5 , 6 . The disease also represents hemorrhagic symptoms characterized by petechial rash on mucosal surfaces, haematuria, epistaxis and gum bleeding 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…CCHFV causes a fatal human infection with high mortality rate. Onset of disease coincides with sudden fever, myalgia, dizziness and bodyache leading to nausea, vomiting, diarrhoea, neural impairments, kidney and liver failure after 5th day of illness that is associated with higher mortality 5 , 6 . The disease also represents hemorrhagic symptoms characterized by petechial rash on mucosal surfaces, haematuria, epistaxis and gum bleeding 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of cells originating from invertebrates to vertebrates has so far been demonstrated to be susceptible to CCHFV [35][36][37]. Although it was previously shown that the liver is one of the primary replication sites of CCHFV [14,38,39], the virus has systematically spread to other tissues such as the kidney [20][21][22]. Since human and mammalian kidney cell lines such as human adrenal gland/cortex (SW-13), rhesus monkey kidney (LLC-MK2), or Syrian golden hamster kidney (BHK-21) are among the most commonly used cells for in vitro CCHFV research [16][17][18], in this study we used kidney cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, kidneys are also affected during CCHFV infections in humans, with evidence for direct virally-induced damage in acute renal failure [ 20 , 21 ]. Furthermore, renal failure is usually related to higher mortality rates in human infections [ 22 ].…”
Section: Introductionmentioning
confidence: 99%